Competition policy and regulation recent developments in China, the US and Europe - Faure, Michael; Zhang, Xinzhu; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2011)
This unique book considers competition policy and regulation in light of the recent introduction of the anti-monopoly law in China. It addresses the relevance of competition policy for China from a broad theoretical and practical perspective, bringing together lawyers and economists from China, Europe and the US to provide an integrated law and economics approach.
pt. 1. General issues -- pt. 2. Competition law and administrative monopolies -- pt 3. Industrial and professional regulation -- pt. 4. Merger control -- pt. 5. Substantive competition law : cartels, abuse of dominance and predation -- pt. 6. Conclusions : future look.
Includes bibliographical references and index.
Keywords: Competition -- China; Competition -- Europe; Competition -- United States; Electronic books